Regulation of fibronectin and collagens type I, III and VI by TNF-α, TGF-β, IL-13, and tofacitinib - Frederik S. Gillesberg; Martin Pehrsson; Anne-Christine Bay-Jensen; Peder Frederiksen; Morten Karsdal; Bent W. Deleuran; Tue W. Kragstrup; Satoshi Kubo; Yoshiya Tanaka; Joachim H. Mortensen (Scientific Reports)
Abstract Understanding how inflammatory cytokines influence profibrogenic wound healing responses in fibroblasts is important for understanding the pathogenesis of fibrosis. TNF-α and IL-13 are key cytokines in Th1 and Th2 immune responses, respectively, while TGF-β1 is the principal pro-fibrotic mediator. We show that 12-day fibroblast culture with TNF-α or IL-13 induces fibrogenesis, marked by progressively increasing type III and VI collagen formation, and that TGF-β1 co-stimulation amplifies these effects. Tofacitinib substantially reduced the formation of ECM proteins in response to IL-13, while fibrogenesis in response to TNF-α or TGF-β1 was marginally inhibited. The in vitro findings were supported by clinical observations in patients with active rheumatoid arthritis, which had elevated serum type III collagen formation, indicating ongoing fibrogenesis during inflammation. After 48–60 weeks of tofacitinib treatment, type III collagen degradation, aswell as formation, were significantly decreased compared to baseline, highlighting dual anti-inflammatory and anti-fibrogenic effects of tofacitinib. In contrast, other anti-inflammatory treatments including methotrexate, adalimumab and tocilizumab demonstrated anti-inflammatory effects only. Our results highlight fibro-inflammatory profiles associated with TNF-α or IL-13 stimulation, both alone and in combination with TGF-β1, and support the use of tofacitinib as an anti-fibrogenic treatment in chronic inflammatory conditions.